2015
DOI: 10.1007/s10620-015-3917-0
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin Therapy in Patients with Refractory Ulcerative Colitis: A Case Series

Abstract: Background and AimsAdrenomedullin (AM) is a multifunctional biologically active peptide that has an ameliorative effect against inflammatory bowel disease in several experimental models. We reported the first case where AM infusion dramatically improved symptoms and colonoscopy findings in patients with refractory ulcerative colitis (UC). To confirm the reproducibility of the efficacy and safety of AM infusion, this pilot study evaluated the clinical feasibility of intravenous administration of AM in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…Indeed, the safety of hemodynamic parameters was confirmed in a previous exploratory clinical study, where AM was infused at a dose of 9 ng/kg/ min for 8 h in patients with UC. 11 In the single-dose administration study, significant increases in PR were observed in the medium-and high-dose AM groups, but this did not appear to be dose-dependent (Table 2). SBP and DBP were decreased during the latter half of the infusion process, but similar decreases were observed in the placebo group.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Indeed, the safety of hemodynamic parameters was confirmed in a previous exploratory clinical study, where AM was infused at a dose of 9 ng/kg/ min for 8 h in patients with UC. 11 In the single-dose administration study, significant increases in PR were observed in the medium-and high-dose AM groups, but this did not appear to be dose-dependent (Table 2). SBP and DBP were decreased during the latter half of the infusion process, but similar decreases were observed in the placebo group.…”
Section: Discussionmentioning
confidence: 90%
“…[5][6][7][8][9][10] Furthermore, AM previously displayed considerable effects in seven patients with UC in an exploratory clinical study. 11 AM has also shown high efficacy in the treatment of intractable Crohn's disease with a loss of response to infliximab. 12 These data strongly suggest that AM is a novel potent therapeutic agent for IBD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AM has a protective role in gastrointestinal diseases, including IBD, and its administration in rodents (Ashizuka et al, 2009) and humans (Ashizuka et al, 2013, 2016) ameliorates the severity of these gut pathologies, emerging as a new promising therapeutic alternative. However, these results should be considered with care since IBD patients have an elevated risk of developing colitis-associated CRC, and the involvement of AM in tumor progression has become evident in the last years (Larráyoz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a first clinical trial on the intravenous injection of ADM in patients suffering from acute myocardial infarction showed an improvement of wall motion and infarct size, suggesting a beneficial treatment in combination with percutaneous coronary intervention [203]. Recently, intravenous infusion of ADM has also been reported to exhibit powerful effects in the treatment of ulcerative inflammatory bowel disease [204].…”
Section: Adrenomedullin In Clinical Trialsmentioning
confidence: 99%